Impact of thrombus length on recanalization and clinical outcome following mechanical thrombectomy in acute ischemic stroke - Seker, Fatih; Pfaff, Johannes; Wolf, Marcel; Schönenberger, Silvia; Nagel, Simon; Herweh, Christian; Pham, Mirko; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2017)
Purpose The impact of thrombus length on recanalization in IV thrombolysis for acute intracranial artery occlusion has been well studied. Here we analyzed the influence of thrombus length on the number of thrombectomy maneuvers needed for recanalization, intraprocedural complications, recanalization success, and clinical outcome after mechanical thrombectomy. Methods: We retrospectively analyzed angiographic and clinical data from 72 consecutive patients with acute occlusion of the M1 segment of the middle cerebral artery who were treated with mechanical thrombectomy using stent retrievers. Successful recanalization was defined as a Thrombolysis in Cerebral Infarction score of 2b or 3. Good neurological outcome was defined as a modified Rankin Scale score of ≤2 at 90 days after stroke onset. Results: Mean thrombus length was 13.4±5.2 mm. Univariate binary logistic regression did not show an association of thrombus length with the probability of a good clinical outcome (OR 0.95, 95% CI 0.84 to 1.03, p=0.176) or successful recanalization (OR 0.92, 95% CI 0.81 to 1.05, p=0.225). There was no significant correlation between thrombus length and the number of thrombectomy maneuvers needed for recanalization (p=0.112). Furthermore, thrombus length was not correlated with the probability of intraprocedural complications (p=0.813), including embolization in a new territory (n=3). Conclusions: In this study, thrombus length had no relevant impact on recanalization, neurological outcome, or intraprocedural complications following mechanical thrombectomy of middle cerebral artery occlusions. Therefore, mechanical thrombectomy with stent retrievers can be attempted with large clots.